DNA Nanoelectronics: Highly Conductive Thin Uniform Gold‐Coated DNA Nanowires (Adv. Mater. 26/2018). Issue 26 (22nd June 2018) - Stern, Avigail; Eidelshtein, Gennady; Zhuravel, Roman; Livshits, Gideon I.; Rotem, Dvir; Kotlyar, Alexander; Porath, Danny
Abstract : Bottom‐up fabrication of electric circuits and devices is highly sought after. The self‐assembly properties of DNA, along with the ability to metallize it, make these molecules advantageous for such fabrication. In article number1800433, Alexander Kotlyar, Danny Porath, and co‐workers present an improved method for thinly coating DNA with gold, along with pioneering detailed electrical characterization of the formed wires.